Fungal Planet description sheets: 1614-1696 - Crous, P W; Jurjević, Ž; Balashov, S; De la Peña-Lastra, S; Mateos, A; Pinruan, U; Rigueiro-Rodríguez, A; Osieck, E R; Altés, A; Czachura, P; Esteve-Raventós, F; Gunaseelan, S; et al. (Fungal systematics and evolution, 2024)
Novel species of fungi described in this study include those from various countries as follows: Australia, Baobabopsis sabindy in leaves of Eragrostis spartinoides, Cortinarius magentiguttatus among deep leaf litter, Laurobasidium azarandamiae from uredinium of Puccinia alyxiae on Alyxia buxifolia, Marasmius pseudoelegans on well-rotted twigs and litter in mixed wet sclerophyll and subtropical rainforest. Bolivia, Favolaschia luminosa on twigs of Byttneria hirsuta, Lecanora thorstenii on bark, in savannas with shrubs and trees. Brazil, Asterina costamaiae on leaves of Rourea bahiensis, Purimyces orchidacearum (incl. Purimyces gen. nov.) as root endophyte on Cattleya locatellii. Bulgaria, Monosporascus bulgaricus and Monosporascus europaeus isolated from surface-sterilised, asymptomatic roots of Microthlaspi perfoliatum. Finland, Inocybe undatolacera on a lawn, near Betula pendula. France, Inocybe querciphila in humus of mixed forest. Germany, Arrhenia oblongispora on bare soil attached to debris of herbaceous plants and grasses. Greece, Tuber aereum under Quercus coccifera and Acer sempervirens. India, Alfoldia lenyadriensis from the gut of a Platynotus sp. beetle, Fulvifomes subramanianii on living Albizzia amara, Inosperma pavithrum on soil, Phylloporia parvateya on living Lonicera sp., Tropicoporus maritimus on living Peltophorum pterocarpum. Indonesia, Elsinoe atypica on leaf of Eucalyptus pellita. Italy, Apiotrichum vineum from grape wine, Cuphopyllus praecox among grass. Madagascar, Pisolithus madagascariensis on soil under Intsia bijuga. Netherlands, Cytosporella calamagrostidis and Periconia calamagrostidicola on old leaves of Calamagrostis arenaria, Hyaloscypha caricicola on leaves of Carex sp., Neoniesslia phragmiticola (incl. Neoniesslia gen. nov.) on leaf sheaths of standing dead culms of Phragmites australis, Neptunomyces juncicola on culms of Juncus maritimus, Zenophaeosphaeria calamagrostidis (incl. Zenophaeosphaeria gen. nov.) on culms of Calamagrostis arenaria. Norway, Hausneria geniculata (incl. Hausneria gen. nov.) from a gallery of Dryocoetes alni on Alnus incana. Pakistan, Agrocybe auriolus on leaf litter of Eucalyptus camaldulensis, Rhodophana rubrodisca in nutrient-rich loamy soil with Morus alba. Poland, Cladosporium nubilum from hypersaline brine, Entomortierella ferrotolerans from soil at mines and postmining sites, Pseudopezicula epiphylla from sooty mould community on Quercus robur, Quixadomyces sanctacrucensis from resin of Pinus sylvestris, Szafranskia beskidensis (incl. Szafranskia gen. nov.) from resin of Abies alba. Portugal, Ascocoryne laurisilvae on degraded wood of Laurus nobilis, Hygrocybe madeirensis in laurel forests, Hygrocybula terracocta (incl. Hygrocybula gen. nov.) on mossy areas of laurel forests planted with Cryptomeria japonica. Republic of Kenya, Penicillium gorferi from a sterile chicken feather embedded in a soil sample. Slovakia, Cerinomyces tatrensis on bark of Pinus mugo, Metapochonia simonovicovae from soil. South Africa, Acremonium agapanthi on culms of Agapanthus praecox, Alfaria elegiae on culms of Elegia ebracteata, Beaucarneamyces stellenboschensis (incl. Beaucarneamyces gen. nov.) on dead leaves of Beaucarnea stricta, Gardeniomyces kirstenboschensis (incl. Gardeniomyces gen. nov.) rotting fruit of Gardenia thunbergia, Knufia dianellae on dead leaves of Dianella caerulea, Lomaantha quercina on twigs of Quercus suber. Melanina restionis on dead leaves of Restio duthieae, Microdochium buffelskloofinum on seeds of Eragrostis cf. racemosa, Thamnochortomyces kirstenboschensis (incl. Thamnochortomyces gen. nov.) on culms of Thamnochortus fraternus, Tubeufia hagahagana on leaves of Hypoxis angustifolia, Wingfieldomyces cypericola on dead leaves of Cyperus papyrus. Spain, Geastrum federeri in soil under Quercus suber and Q. canariensis, Geastrum nadalii in calcareous soil under Juniperus, Quercus, Cupressus, Pinus and Robinia, Hygrocybe garajonayensis in laurel forests, Inocybe cistophila on acidic soil under Cistus ladanifer, Inocybe sabuligena in a mixed Quercus ilex subsp. ballota/Juniperus thurifera open forest, Mycena calongei on mossy bark base of Juniperus oxycedrus, Rhodophana ulmaria on soil in Ulmus minor forest, Tuber arriacaense in soil under Populus pyramidalis, Volvariella latispora on grassy soils in a Quercus ilex ssp. rotundifolia stand. Sweden, Inocybe iota in alpine heath on calcareous soil. Thailand, Craterellus maerimensis and Craterellus sanbuakwaiensis on laterite and sandy soil, Helicocollum samlanense on scale insects, Leptosporella cassiae on dead twigs of Cassia fistula, Oxydothis coperniciae on dead leaf of Copernicia alba, Russula mukdahanensis on soil, Trechispora sangria on soil, Trechispora sanpatongensis on soil. Türkiye, Amanita corylophila in a plantation of Corylus avellana. Ukraine, Pararthrophiala adonis (incl. Pararthrophiala gen. nov.) on dead stems of Adonis vernalis. USA, Cladorrhinum carnegieae from Carnegiea gigantea, Dematipyriformia americana on swab from basement wall, Dothiora americana from outside air, Dwiroopa aeria from bedroom air, Lithohypha cladosporioides from hospital swab, Macroconia verruculosa on twig of Ilex montana, associated with black destroyed ascomycetous fungus and Biatora sp., Periconia floridana from outside air, Phytophthora fagacearum from necrotic leaves and shoots of Fagus grandifolia, Queenslandipenidiella californica on wood in crawlspace. Morphological and culture characteristics are supported by DNA barcodes. Citation: Crous PW, Jurjević Z, Balashov S, De la Peña-Lastra S, Mateos A, Pinruan U, Rigueiro-Rodríguez A, Osieck ER, Altés A, Czachura P, Esteve-Raventós F, Gunaseelan S, Kaliyaperumal M, Larsson E, Luangsa-ard JJ, Moreno G, Pancorbo F, Piątek M, Sommai S, Somrithipol S, Asif M, Delgado G, Flakus A, Illescas T, Kezo K, Khamsuntorn P, Kubátová A, Labuda R, Lavoise C, Lebel T, Lueangjaroenkit P, Maciá-Vicente JG, Paz A, Saba M, Shivas RG, Tan YP, Wingfield MJ, Aas T, Abramczyk B, Ainsworth AM, Akulov A, Alvarado P, Armada F, Assyov B, Avchar R, Avesani M, Bezerra JL, Bhat JD, Bilański P, Bily DS, Boccardo F, Bozok F, Campos JC, Chaimongkol S, Chellappan N, Costa MM, Dalecká M, Darmostuk V, Daskalopoulos V, Dearnaley J, Dentinger BTM, De Silva NI, Dhotre D, Carlavilla JR, Doungsa-ard C, Dovana F, Erhard A, Ferro LO, Gallegos SC, Giles CE, Gore G, Gorfer M, Guard FE, Hanson S-A, Haridev P, Jankowiak R, Jeffers SN, Kandemir H, Karich A, Kisło K, Kiss L, Krisai-Greilhuber I, Latha KPD, Lorenzini M, Lumyong S, Manimohan P, Manjón JL, Maula F, Mazur E, Mesquita NLS, Młynek K, Mongkolsamrit S, Morán P, Murugadoss R, Nagarajan M, Nalumpang S, Noisripoom W, Nosalj S, Novaes QS, Nowak M, Pawłowska J, Peiger M, Pereira OL, Pinto A, Plaza M, Polemis E, Polhorský A, Ramos DO, Raza M, Rivas-Ferreiro M, Rodriguez-Flakus P, Ruszkiewicz-Michalska M, Sánchez A, Santos A, Schüller A, Scott PA, Şen İ, Shelke D, Śliwa L, Solheim H, Sonawane H, Strašiftáková D, Stryjak-Bogacka M, Sudsanguan M, Suwannarach N, Suz LM, Syme K, Taşkın H, Tennakoon DS, Tomka P, Vaghefi N, Vasan V, Vauras J, Wiktorowicz D, Villarreal M, Vizzini A, Wrzosek M, Yang X, Yingkunchao W, Zapparoli G, Zervakis GI, Groenewald JZ (2024). Fungal Planet description sheets: 1614-1696. Fungal Systematics and Evolution 13: 183-440. doi: 10.3114/fuse.2024.13.11.
Keywords: ITS nrDNA barcodes; new taxa systematics; LSU